Natural killer T cells mediate inflammation in the bile ducts. Issue 6 (November 2018) - Berntsen, N.; Fosby, B.; Tan, C.; Reims, H.; Ogaard, J.; Jiang, X.; Schrumpf, E.; Valestrand, L.; Karlsen, T.; Line, P.-D.; Blumberg, R.; Melum, E.
Abstract Cholangiocytes function as antigen-presenting cells with CD1d-dependent activation of natural killer T (NKT) cells in vitro. NKT cells may act both pro- and anti-inflammatory in liver immunopathology. We explored this immune pathway and the antigen-presenting potential of NKT cells in the bile ducts by challenging wild-type andCd1d −/− mice with intrabiliary injection of the NKT cell activating agent oxazolone. Pharmacological blocking of CD1d-mediated activation was performed with a monoclonal antibody. Intrabiliary oxazolone injection in wild-type mice caused acute cholangitis with significant weight loss, elevated serum levels of alanine transaminase, aspartate transaminase, alkaline phosphatase and bilirubin, increased histologic grade of cholangitis and number of T cells, macrophages, neutrophils and myofibroblasts per portal tract after 7 days. NKT cells were activated after intrabiliary injection of oxazolone with upregulation of activation markers.Cd1d −/− and wild-type mice pretreated with antibody blocking of CD1d were protected from disease. These findings implicate that cells in the bile ducts function as antigen-presenting cells in vivo and activate NKT cells in a CD1d-restricted manner. The elucidation of this biliary immune pathway opens up for potentially new therapeutic approaches for cholangiopathies.